Interferon-γ from Brain Leukocytes Enhances Meningitis by Type 4 Streptococcus pneumoniae - Pettini, Elena; Fiorino, Fabio; Cuppone, Anna Maria; Iannelli, Francesco; Medaglini, Donata; Pozzi, Gianni (Frontiers in Microbiology, 2015)
Streptococcus pneumoniae is the leading cause of bacterial meningitis. Pneumococcal meningitis is a life-threatening disease with high rates of mortality and neurological sequelae. Immune targeting of S. pneumoniae is essential for clearance of infection; however, within the brain, the induced inflammatory response contributes to pathogenesis. In this study we investigate the local inflammatory response and the role of IFN-γ in a murine model of pneumococcal meningitis induced by intracranial injection of type 4 S. pneumoniae. Lymphoid and myeloid cell populations involved in meningitis, as well as cytokine gene expression, were investigated after infection. Animals were treated with a monoclonal antibody specific for murine IFN-γ to evaluate its role in animal survival. Intracranial inoculation of 3×104 colony-forming units of type 4 strain TIGR4 caused 75% of mice to develop meningitis within 4 days. The amount of lymphocytes, NK cells, neutrophils, monocytes and macrophages in the brain increased 48 hours post infection. IFN-γ mRNA levels were about 240-fold higher in brains of infected mice compared to controls. Pro-inflammatory cytokines such as IL-1β and TNF-α, and TLR2 were also upregulated. In vivo treatment with anti-IFN-γ antibody increased survival of infected mice. This study shows that IFN-γ produced during meningitis by type 4 S. pneumoniae enhances bacterial pathogenesis exerting a negative effect on the disease outcome.